Code-switching in Malaysian classroom as the microcosm of society in socio-cultural context / Caesar DeAlwis - DeAlwis, Caesar (Universiti Teknologi MARA Cawangan Sarawak, 2019)
Teaching English as a second language is distinctive because of its specific needs. Facing a competitive market, students from young need to acquire communicative skills in English for future studies and employment. However, outside the classroom, it is no longer just a norm for multilingual societies to code- switch but rather code–switching has become a part of their unique speech style. As such in the teaching service, ESL teachers may not be able to isolate themselves from such a social norm. The question of whether English language teachers should code-switch in the classrooms has been much debated with most researchers maintained that teachers who code-switch, may end up invalidating the second language of students. Cases of students having low level of English proficiency to understand a teacher’s input or students too reluctant to participate in learning because they feel incompetent in the English language classrooms are common concerns to all ESL teachers. Therefore, should the ESL teacher’s code-switch to make them understood? Or should the English only policy be used and different from the wider multi-cultural linguistic environment? The data collection technique used in this study was audio recording and unstructured interview with 10 TESL teachers, teaching in Sarawak, Malaysia. The perceptions of ESL teachers who generally suggest that code-switching is a common phenomenon and not interference in ELT are pertinent issues to be discussed.